(untitled) (Revista Cocar, 2024)
A pesquisa busca identificar concepções e estratégias de professores e auxiliares da Educação Infantil relacionadas ao trabalho coletivo e à vivência da figura de referência com as crianças. Examinam-se os indícios de (des)assossegos causados pela (co)responsabilidade do cuidado e educação na Educação Infantil. Por meio de um estudo qualitativo e exploratório com dez profissionais, a pesquisa aborda a problemática das origens do (des)assossego na partilha de (co)responsabilidades no cotidiano da primeira infância. Conclui que, ao fortalecer o grupo, favorecendo a formação integral das crianças e o bem-estar de todos, é possível reinterpretar convívios e realizar a partilha de experiências como adulto referência para as crianças. Palavras-chave: Referência compartilhada; Professores; Auxiliares. Abstract The research aims to identify the conceptions and strategies of teachers and assistants in Early Childhood Education related to collective work and the experience of being a reference figure for children. It examines the signs of (dis)comfort caused by the (co)responsibility of care and education in Early Childhood Education. Through a qualitative and exploratory study involving ten professionals, the research addresses the issue of the origins of (dis)comfort in the sharing of (co)responsibilities in the daily life of early childhood. It concludes that by strengthening the group, promoting the comprehensive development of children, and ensuring the well-being of all, it is possible to reinterpret interactions and share experiences as a reference adult for the children. Keywords: Shared reference; Teachers; Assistants.